Serotonin is involved in the psychostimulant and hypothermic effect of 4-methylamphetamine in rats. (17th March 2015) - Rubio, Mar; López-Arnau, Raúl; Pubill, David; Escubedo, Elena; Camarasa, Jorge
Highlights: 4-methylamphetamine increased locomotor activity and induced hypothermia in rats. The increase in the locomotor activity involves both dopamine and serotonin. The hypothermic response reached a maximum 45 min after injection. The hypothermia is due to an activation of postsynaptic 5-HT1A receptors. Abstract: 4-Methylamphetamine (4-MA) has recently emerged as a designer drug of abuse in Europe and it is consumed always with amphetamine. There have been reported some deaths and non-fatal intoxications related to 4-MA. We investigated the changes in locomotor activity and body temperature after 4-MA administration to male Sprague–Dawley rats. Our experiments were carried out at a normal or high ambient temperature. 4-MA (2.5–10 mg/Kg, given subcutaneously) increased, in a dose-dependent manner, the horizontal locomotor activity that was significantly reduced by ketanserin, p -cholorophenylalanine (pCPA) or haloperidol, but not by pindolol. In addition, we have studied the effect of 4-MA on core body temperature by means of an implanted electronic thermograph, enabling continuous measurement of body temperature. We observed a dose-dependent hypothermic response to 4-MA that reached a maximum 45 min after a single injection. We also evidenced slight tachyphylaxis to the hypothermic effect when 4-MA was administered four times in a 2 h interval. The pre-treatment of animals with pCPA or pindolol, but not with ketanserin, fully abolished the hypothermic effect of 4-MA. With all that, we conclude that hypothermia induced by 4-MA is due to the release of 5-HT which activates postsynaptic 5-HT1A receptors.